Visions for Intercultural Music Teacher Education - Westerlund, Heidi; Karlsen, Sidsel; Partti, Heidi (Landscapes: the Arts, Aesthetics, and Education, 2020)
This open access book highlights the importance of visions of alternative futures in music teacher education in a time of increasing societal complexity due to increased diversity. There are policies at every level to counter prejudice, increase opportunities, reduce inequalities, stimulate change in educational systems, and prevent and counter polarization. Foregrounding the intimate connections between music, society and education, this book suggests ways that music teacher education might be an arena for the reflexive contestation of traditions, hierarchies, practices and structures. The visions for intercultural music teacher education offered in this book arise from a variety of practical projects, intercultural collaborations, and cross-national work conducted in music teacher education. The chapters open up new horizons for understanding the tension-fields and possible discomfort that music teacher educators face when becoming change agents. They highlight the importance of collaborations, resilience and perseverance when enacting visions on the program level of higher education institutions, and the need for change in re-imagining music teacher education programs.